Palm Oil Transportation Study Using Jumbo and Regular Dump Trucks - Jessen Spinoza Putra Komawi; Maswadi Maswadi; Shenny Oktoriana (TIN: Terapan Informatika Nusantara, 2026)
This study aims to analyze the differences in transportation cycle time and operational costs between jumbo-bed dump trucks and standard-bed dump trucks in transporting fresh fruit bunches (FFB) of oil palm from the ramp to the processing plant in Parindu District, Sanggau Regency. The results show that standard-bed dump trucks have shorter transportation cycle times compared to jumbo-bed dump trucks. This is due to their smaller load capacity, which makes the loading, transportation, unloading, and return processes more efficient. In contrast, jumbo-bed dump trucks require longer cycle times because their larger load volumes demand longer working durations for each transportation cycle. In addition, the operational costs of jumbo-bed dump trucks are higher than those of standard-bed dump trucks due to greater fuel consumption, higher maintenance costs, and higher depreciation per transportation cycle. Cost analysis results indicate that the transportation cost per kilogram of FFB using standard-bed dump trucks is more economical, with a cost difference of IDR 44,000.00 per kilogram compared to jumbo-bed dump trucks. Therefore, the use of standard-bed dump trucks is considered more efficient in terms of both transportation time and cost for oil palm FFB.